Kontruksi Berita Portal asahankab.go.id Tentang Sekda Tutup Turnamen Old Crack PWL Asahan 2023: Analisis Framing Perspektif Zhondang pan – Gerald M Kosicki - Ryan Aulia Arif; Solihah Titin Sumanti (Mahesa Research Center, 2023)
The reason for this study is to figure out the outlining investigation (casing or bundling) of political news on the asahankab.go.id media entry with respect to the conclusion of the PWI Asahan 2023 Old Break football competition. This exploration utilizes a constructivist approach, which is an investigation that sees talk because of the development of social reality. This exploration is named library research; information gathered with citing, adjusting, and examining utilizing outlining investigation with delegate writing that has significance to the issue talked about, then, at that point, evaluated and closed. After holding a discussion on the framing analysis of the Regional Secretary Close the PWI Asahan 2023 Old Crack Tournament using the Zhongdang Pan and Gerald method. M. Kosicki. The author finds, in terms of framing devices (syntactic, script, thematic and rhetorical), shows asahankab.go.id in constructing social reality, especially news about The closing of Old Crack PWI Asahan 2023 is quite dominant in alignments the media.